Diversity of Insects with Potential as Pests on Sweet Corn (Zea mays L. Saccharata Sturt) in Telagawaru Village, Labuapi District, West Lombok Regency - Priandani, Livia Tara; Haryanto, Hery; Jihadi, Amrul (Jurnal Biologi Tropis, 2025)
Sweet corn (Zea mays L. Saccharata Sturt) is one of the cereal crops that serves as an important food source in Indonesia, yet its productivity is often disrupted by pest attacks. This study aims to determine the diversity, dominance, and evenness of pests on sweet corn (Zea mays L. Saccharata Sturt). The research was conducted in Telagawaru Village, Labuapi District, West Lombok Regency, from November 2024 to January 2025. A descriptive method with a field survey technique was applied at two cultivation sites with a total area of 725 m². Each site was divided into five observation blocks measuring 5 × 5 meters, with data collection carried out using yellow pan traps and pitfall traps over five weekly observations. The results showed a total of 452 pest individuals consisting of 28 genera, 19 families, and 6 orders (Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, and Orthoptera). Site 1 had a Shannon-Wiener diversity index (H') = 2.69, Simpson dominance index (D) = 0.095, and evenness index (E) = 0.527, with the dominant genus being Bactrocera sp. (41 individuals). Site 2 recorded (H') = 2.12, (D) = 0.222, and (E) = 0.332, dominated by Bactrocera sp. (108 individuals). Both sites indicated stable and balanced ecological conditions, showing high potential for the application of sustainable biological control.